Assessment of Immunization Coverage of Pediatric Population in Telangana - Girish Manohar Chavan; Mavatkar MV (Medsci Publications, 2019)
Background: The immunization coverage in India is far away from acceptable level with complete immunization coverage being only 62% at the national level. Targeting efforts towards poor per- forming areas and knowing the determinants of non- immunization and dropouts offers a quick solution. Objectives: To assess the immunization coverage of antenatal women and children below 2 years of age and its associated fac- tors in Mehboobnagar District of Telengana State. Methods: Study A Cross Sectional study, where, a list of the im- munization session sites were obtained and convenient sampling for immunization session site was done. Around 122 children be- tween 0-23 months were screened for immunization by house to house survey method. Entire data was collected and analyzed by using SPSS software. Results: Overall 83.60% of the children were fully immunized. Maximum Children (27.86%) belonged to 11-15 month of age. About 25% of the children belonged to polio high risk area. The predominant reasons for default of vaccination was 'sick of child','caregiver being out of station, 'post vaccination minor illness and swelling', 'Poor awareness about date of immunization'. Conclusion: Overall, coverage of immunization is not as per goal set under Mission Indradhanush.